Defining flood risk management strategies: A systems approach. (August 2020) - Mai, Thanh; Mushtaq, Shahbaz; Reardon-Smith, Kate; Webb, Paul; Stone, Roger; Kath, Jarrod; An-Vo, Duc-Anh
Abstract: Recent years have seen a growing recognition of and attention to strengthening community flood resilience as a key leverage for achieving sustainable flood risk management. The literature on the success of focusing on ex-post responses to flood events shows poor outcomes in mitigating flood risks across the board. Here, we employ systems thinking to conceptualise the dynamics underlying interactions among endogenous characteristics of the flood-prone community, and apply this, as a case study example, to the regional township of Roma in inland Queensland, Australia—a location that has experienced significant flooding in recent decades. Our results show that current flood mitigation policies are likely to be maladaptive due to unintended consequences that ultimately undermine the effectiveness of the interventions in the longer term. Based on our analysis, we conclude that integrated flood risk management, effected through well-targeted proactive investments—such as investment in infrastructure; technology advances; capacity improvements; shifts in systems, management practices and behaviour—and risk transfer (insurance) options, provide opportunities for reducing future relief and recovery costs and increasing fiscal stability and the long term well-being of communities in the face of increasing climate variability and flood risk under climate change. Conceptualisation and visualisation of the flood risk system, as exemplified in this paper, provides insights which might help to guide more cost-effective and sustainable flood risk mitigation investment in flood-prone communities.